Community-based delivery of HIV treatment in Zambia: costs and outcomes. (2nd February 2021) - Nichols, Brooke E.; Cele, Refiloe; Jamieson, Lise; Long, Lawrence C.; Siwale, Zumbe; Banda, Patrick; Moyo, Crispin; Rosen, Sydney
Abstract : Objective: The aim is to determine the total annual cost per patient treated and total cost per patient retained on antiretroviral therapy in Zambia in conventional care in facilities and across community-based differentiated service delivery (DSD) models. Design: Economic evaluation was conducted using retrospective electronic record review. Twenty healthcare facilities (13 with DSD models and 7 as comparison sites) in six of Zambia's 10 provinces were considered. Methods: All individuals on antiretroviral therapy (ART) >18 years old at the study sites were enrolled in a DSD model or conventional care by site type, respectively, with at least 12 months of follow-up data. Accessing care through DSD models [community adherence groups (CAGs), urban adherence groups (UAGs), home ART delivery and care, and mobile ART services] or facility-based conventional care with 3-monthly visits. Total annual cost per patient treated and the annual cost per patient retained in care 12 months after model enrolment. Retention in care was defined as attending a clinic visit at 12 months ± 3 months. Results: The DSD models assessed cost more per patient/year than conventional care. Costs ranged from an annual 116 to 199 for the DSD models, compared with 100 for conventional care. CAGs and UAGs increased retention by 2 and 14%, respectively. All DSD models cost more per patient retained at 12 months than conventional care. The CAG had the lowest cost/patient retained for DSD models (140–157). Conclusions: Although they achieve equal or improved retention in care, out-of-facility models of ART were more expensive than conventional care. Abstract : Supplemental Digital Content is available in the text